Treatment of biliary leakages after cholecystectomy and importance of stricture development in the main bile duct injury - Erkan PARLAK; Bahattin ÇİÇEK and Selçuk DİŞİBEYAZ and Sedef ÖZDAL KURAN and Dilek OĞUZ and Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-